TANTANGAN DAN PELUANG BELAJAR DI KOREA SELATAN PERSPEKTIF MAHASISWA IISMA - Rabsy, M. Ferdi (JURNAL MENATA, 2025)
The Indonesian International Student Mobility Awards (IISMA) program provides Indonesian students with the opportunity to experience international education, particularly in South Korea, known for its modern education system, advanced technology, and rich culture. This article explores the challenges and opportunities faced by IISMA students in South Korea, including adaptation to differences in curriculum, culture, and language. The research method involves analyzing personal experiences through internships, industrial visits, and participation in academic programs.  The findings reveal that students face significant challenges, such as academic pressure, language barriers, and cultural differences, which demand high adaptability. However, the opportunities offered are substantial, including the development of cross-cultural skills, enhanced global insights, and direct exposure to the professional world through internships at Lotte Hotel Ulsan, training at Air Busan Headquarters, and industrial visits to locations such as Kweon Do Yeong Aloe Farm and Ulsan Jeil Hospital.  In conclusion, the IISMA program helps students develop academic and professional potential, build adaptive character, and improve global competitiveness. This experience contributes to shaping a generation of Indonesian youth with an international perspective, ready to face the challenges of globalization.